2016
DOI: 10.4103/0973-1075.173956
|View full text |Cite
|
Sign up to set email alerts
|

Myofacial trigger points in advanced cancer patients

Abstract: Myofascial pain syndrome is started to be recognized as one of important factors of pain in cancer patients. However, no reports on features of myofascial trigger points were found in terminally-ill cancer populations. This time, we encountered 5 patients with myofascial pain syndrome and terminal cancer in whom delirium developed due to increased doses of opioid without a diagnosis of myofascial pain syndrome on initial presentation. The delirium subsided with dose reductions of opioid and treatment of myofas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 15 publications
(14 reference statements)
0
9
0
4
Order By: Relevance
“…The ndings of this study may be useful to raise awareness of psychosomatic-prone MPS in patients with incurable cancer. MPS in patients with incurable cancer is often overlooked and is a common cause of opioid-induced delirium (16). Furthermore, medical professionals may consider pain that is exacerbated by stress as psychogenic pain.…”
Section: Discussionmentioning
confidence: 99%
“…The ndings of this study may be useful to raise awareness of psychosomatic-prone MPS in patients with incurable cancer. MPS in patients with incurable cancer is often overlooked and is a common cause of opioid-induced delirium (16). Furthermore, medical professionals may consider pain that is exacerbated by stress as psychogenic pain.…”
Section: Discussionmentioning
confidence: 99%
“…It is usually managed with conservative treatment such as physical therapy and medication. In severe cases, the pain needs to be alleviated by inactivating the trigger point and restoring muscle function.1,7,9) Various studies have reported that pain due to cancer can create trigger points, that trigger points can coexist with cancer pain, and that pain may be exacerbated by cancer [5,10]. Especially in advanced cancer patients, opioids alone may not adequately control pain or the side effects of the opioids may prevent a satisfactory dosage from being attained [11-13].…”
Section: Discussionmentioning
confidence: 99%
“…Myofascial pain syndrome may develop abruptly or gradually, and may not respond to treatments that are effective for other sources of pain. As an example, opioids, which are highly effective for treating most types of cancer-related pain, are often ineffective in relieving myofascial pain (3). Furthermore, myofascial pain may persist even after successful neurolytic blocks, targeting the visceral component of pancreatic cancer.…”
Section: Quadratus Lumborum Block For Back Pain Related To Pancreatic Cancer -A Report Of Two Casesmentioning
confidence: 99%
“…MPS is frequently diagnosed in patients with cancer pain (3,4), in whom it is thought to be triggered by several mechanisms, including direct muscle invasion by the tumor, muscle irritation by metabolites secreted into the milieu of the tumor, sarcopenia accompanying deconditioning in advanced disease, prolonged bed rest, and by some anticancer treatments such as irradiation and surgery.…”
mentioning
confidence: 99%